2008
DOI: 10.1080/13803390701819044
|View full text |Cite
|
Sign up to set email alerts
|

The primary cognitive deficit among males with fragile X-associated tremor/ataxia syndrome (FXTAS) is a dysexecutive syndrome

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder associated with a premutation trinucleotide repeat expansion in the fragile X mental retardation 1 gene (FMR1). Symptoms include gait ataxia, action tremor, and cognitive impairment. The objectives of the study were to clarify the nature of the dysexecutive syndrome observed in FXTAS and to assess the contribution of executive impairment to deficits in nonexecutive cognitive functions. Compared to controls, men with FXTAS demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 87 publications
12
89
2
Order By: Relevance
“…Brega and colleagues suggested that executive dysfunction might mediate impaired performance on tests in other cognitive domains [25]. The appearance of executive dysfunction in male carriers prior to developing FXTAS remains unclear.…”
Section: Cognitive Deficits In Premutation Carriersmentioning
confidence: 99%
“…Brega and colleagues suggested that executive dysfunction might mediate impaired performance on tests in other cognitive domains [25]. The appearance of executive dysfunction in male carriers prior to developing FXTAS remains unclear.…”
Section: Cognitive Deficits In Premutation Carriersmentioning
confidence: 99%
“…White matter degeneration has been described as the most prominent neuropathologic characteristic of FXTAS, 8 and the presence of normal frontal cortical thickness and neuronal density 8 suggests that cortical degeneration is not the initial event leading to cognitive dysfunction. Moreover, the similarity of cognitive dysfunction in FXTAS [2][3][4][5][6]18 to a host of known white matter disorders 7 suggests that white matter damage may be a critical determinant of cognitive decline and dementia in this disease. 4 An intriguing implication of this work is that dementia related to primary white matter dysfunction may occur in the setting of neurodegenerative disease.…”
Section: Figure 2 Mrs Voxel Placementmentioning
confidence: 99%
“…associated with the FMR1 premutation, 2,3,18 and with widespread white matter degeneration in FXTAS that includes loss of both myelin and axons. 8 This is the first study to report white matter MRS data in association with cognitive dysfunction in FMR1 premutation carriers.…”
Section: Figure 2 Mrs Voxel Placementmentioning
confidence: 99%
“…There is strong evidence for the existence of a dysexecutive profile in asymptomatic PM-carriers (those without FXTAS) [16][17][18][19]. The male asymptomatic PM-carrier phenotype is currently characterised by impairments in executive processing, with specific deficits in tasks reliant upon working memory, inhibitory processing, visuospatial processing and attentional control [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 97%